COVID-19 and Corporate Governance Performance: Beyond the Financial Metrics (2021)
Corporate governance and more broadly, the performance of corporate boards have traditional been measured using financial metrics. These financial metrics like Return on Investment (ROI), Return on Assets (ROA), Return on Equity (ROE), Earnings and Profitability Ratio (E and P) are ex-post measure of organizations wellbeing or lack thereof arising from corporate board activities. These financial metrics are, for all intents and purposes, self-serving and one-dimensional measure of corporate performance. They do not fully account for the other dimensions of organization responsibilities especially, the social, health and environmental benefits expected from organization’s activities. The COVID-19 and the changing organizational dynamics have made the case for corporate board’s performance to be assessed beyond the usual financial metrics. In this study, we provide a framework that accounts for the various dimensions of organization activities: finance, social and environmental; the so-called Triple-Bottom (TBL) approaches. A TBL-compliance metric was used to track the performance of selected manufacturing firms in Nigeria using a content analytical technique. The result of the analysis showed that majority of the firms performed remarkably well in areas of profitability and economic value creation but performed less satisfactorily in areas of social and environmental sustainability. On aggregate, the sampled firms committed less than 1 percent of their profit after tax on corporate social responsibility while less than 5 percent of the sampled firms scored above average on the TBL-adoption matrix. From the findings of the study we can conclude that manufacturing firms in Nigeria are yet to be fully committed to social and environmental sustainability. The study recommended for a regulatory re-jig away from the usual mandatory declaration of commitment to concrete actions based on measurable indicators on social and environmental sustainability compliance.